Study of Religious Attitudes of Dormitory and Non-dormitory Students - Nabilah, Ebi; Yansyah, Dandi; Arrizki, Ahmad Irfan; Apriani, Elvi (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
Changes in religious behavior are influenced by religious attitudes, including behavior during adolescence. A good religious attitude will lead to good religious behavior. Religious attitudes are formed through direct experience through interaction with various elements of the social environment. Therefore, a person's religious attitude is different in responding to a stimulus, including between dormitory and non-dormitory students. This study aims to determine the level of comparison of religious attitudes between dormitory and non-dormitory students.This research uses descriptive quantitative method. Data was obtained using a questionnaire. Data were analyzed using simple statistics. The sample used was 34 students, consisting of 17 dormitory students and 17 non-boarding students. After the data was processed, the researchers generally analyzed the level of differences in religious attitudes between dormitory and non-dormitory students and the differences in each dimension of religious attitudes. The analysis of the mean scores resulted in the finding that in general, the difference in religious attitudes between dormitory and non-dormitory students was 4.1 > 4.1. Analysis on each dimension is known that from the five dimensions, the level of comparison in the three dimensions is obtained by the dormitory students. The three dimensions are ritual (3.9 > 3.4), mystical (4.5 > 4.3) and intellectual (4.5 > 4.2). Meanwhile, non-boarding students are superior in ideological dimensions (4.0 < 4.2). And the social dimension has the same level of religious attitude (4.3 = 4.3).